Simulation of the Focal Spot of the Accelerator Bremsstrahlung Radiation; IOP Conference Series: Materials Science and Engineering; Vol. 132 : Modern Technologies for Non-Destructive Testing - Sorokin V. B. Vladimir Borisovich (2016, 2016)
Title screen